THE USE OF A HYDROGELS - ACTIVE ADHESIVE POLYMER STAGES, SATURATED CHLORHEXIDINE BIHLYUKONATOM IN REMOVABLE PROSTHETICS TO ACCELERATE THE REGENERATION OF ORAL MUCOSA - N.Y. Komarytsia; O. V. Suberliak; N. B. Semeniuk; U. V. Vovk (Український стоматологічний альманах)
Removable laminar dentures can cause changes in the mucous membranes of the oral cavity (MMOC), which are caused by toxic, chemical, allergic, thermal factors, mechanical trauma of the mucosa and contribute to the appearance of pathogenic microflora, the development of inflammation of the oral mucous membrane. One of the nowadays areas of biomedical materials sciences is the search of new polymers and mineralpolymer compositions that can be used as a medical preparative depot.